The British Nuclear Experience: The Roles of Beliefs, Culture and Identity - John Baylis (Oxford University Press, 2014)
Traditional mainstream explanations tend to stress the importance of factors such as the 'maximization of power', the pursuit of 'national security interests' and the role of 'structure' in a largely anarchic international system. This book does not dismiss these approaches, but argues that British experience suggests that focusing on 'beliefs', 'culture' and 'identity', provides a more useful insight and distinctive interpretation into the process of British nuclear decision making than the more traditional approaches.